Relationship between the velocity of the center of mass and the mechanical work done by the shoulder and hip joints in performing the basket to handstand on parallel bars - Yamada, T.; Sato, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this research was to investigate the relationship between the velocity of the center of mass and the mechanical work done by the shoulder and hip joints in performing the basket to handstand on parallel bars. Twenty-six male elite gymnasts were videotaped at the national championships. Two-dimensional motion analysis technique and inverse dynamics approach were used for calculating the kinematic and kinetic parameters. The negative work done by the shoulder joint significantly related to the velocity of the center of mass at 270 deg. point(r=0.55, p<0.05), but the positive work done by the hip joint had no significant relationship to the velocity(r=0.33, n.s.). Therefore decreasing the negative work done by the shoulder joint was important for better execution of the basket to handstand on parallel bars.